The Effects of FDI Liberalization on Structural Transformation and Demographic Change: Evidence from China - Bilge Erten; Jessica Leight; Lianming Zhu (Institute of Labor Economics (IZA), 2023)
How does foreign direct investment (FDI) liberalization shape structural transformation and demographic change in developing countries? We provide new evidence on this question using five waves of Chinese census data between 1990 and 2015, exploiting quasi-exogenous variation in FDI liberalization induced by multiple waves of regulatory relaxation. We find that counties more exposed to liberalization experience a relative shift out of agricultural employment into manufacturing and services for both men and women. Exposure to FDI liberalization also reduces the probability of marriage, and induces a decline in the birth rate and the share of women with children.
Keywords: F23; F63; J13; 330; foreign direct investment; structural transformation; demographic change; China